Amorphous carbon films doped with silver and chromium to achieve ultra-low interfacial electrical resistance and long-term durability in the application of proton exchange membrane fuel cells. (April 2019) - Zhang, Di; Yi, Peiyun; Peng, Linfa; Lai, Xinmin; Pu, Jibin
Abstract: Amorphous carbon (a-C) films exhibit properties that make them attractive for a wide range of applications in automotive components. Proton exchange membrane fuel cells (PEMFCs) assembled by metallic bipolar plates (BPPs) are promising power sources for new energy vehicles. Harsh environments of PEMFCs require preparing coatings on metallic BPPs to achieve high corrosion resistance and electrical conductivity, and a-C based coatings have the great potential. However, their low stability and high internal stress significantly damage their durability. This work aims to develop a fundamental understanding of the effect of doping Ag and Cr on the performance and durability of a-C based coatings. Experimental results revealed that a-C films doped with Ag and Cr (a-C:Ag:Cr) simultaneously achieve ultra-low interfacial contact resistance (ICR), low internal stresses, and higher stabilities. We also developed an atomistic model by molecular dynamics (MD) to understand certain behaviors of a-C:Ag:Cr. The ultra-low ICR was mainly attributed to Ag nanoclusters embedded in a-C phases, low hardness, and a more graphite-like structure. The enhanced stability was attributed to denser structures and lower internal stresses. MD simulations suggested that the effect of doping Ag or Cr on the surface morphology and internal stress of a-C films may have different mechanisms. Graphical abstract: Image 1